A joint dynamic inventory-slot allocation model for liner shipping using revenue management concepts. (August 2022) - Mehrzadegan, Elaheh; Ghandehari, Mahsa; Ketabi, Saeedeh
Highlights: A dynamic slot allocation model for liner shipping transportation is proposed. Repositioning and leasing of empty containers are included in the model. Empty containers inventories in ports are managed. Services with different prices are available. The model is compared with the FCFS model using a simulation approach. Abstract: In this article, we integrate dynamic slot allocation and inventory management to improve liner shipping decisions. Multi-leg revenue management concepts are used to model the problem of marine transporting full and empty containers. The model considers market distinctions, service diversity, and no-shows. The transportation of empty containers is planned to balance the inventory of empty containers in the ports. The problem is formulated as an integer program. Our objective is to maximize the total profit (revenue from shipping full containers minus the overall costs of transporting, leasing, and holding empty containers). An illustrative example based on Iranian liner shipping is solved, and the sensitivity of the results is analyzed. To evaluate the proposed deterministic model, we compare its results to those of the first come first serve (FCFS) method in a stochastic environment using simulation. A comparison between the proposed and traditional FCFS models shows a significant increase in profit.